Hierarchical block model for seismic processes - Mykulyak, S.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The model based on cellular automata is constructed with regard for two fundamental properties of seismically active areas: a hierarchical block structure and their existence in a state of self-organized criticality. The model reproduces the main empirical properties of seismic processes: the frequency-energy invariance of seismic events (the Gutenberg—Richter law), generalized Omori law for aftershocks, and fractal distribution of hypocenters (epicenters) with power-law dependences of the number of events on distances between hypocenters (epicen ters).